2010
DOI: 10.1186/1476-0711-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of conjugative transfer of plasmid-encoded ISEcp1 - blaCTX-M-15 and aac(6')-lb-cr genes in Enterobacteriaceae at a tertiary care center in Lebanon - role of transferases

Abstract: BackgroundThe frequency of transfer of genes encoding resistance to antimicrobial agents was determined by conjugation in ESBL-producing and/or fluoroquinolone or aminoglycoside resistant Enterobacteriaceae clinical isolates at a tertiary care center in Lebanon. In addition, the role of tra genes encoding transferases in mediating conjugation was assessed.MethodsConjugation experiments were done on 53 ESBL-producing and/or fluoroquinolone resistant E. coli and K. pneumoniae and ESBL-producing S. sonnei isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Those expressing an ESBL phenotype frequently carry genes encoding resistance to other commonly used antimicrobial drug classes (such as aminoglycosides, chloramphenicols, fluoroquinolones, or tetracycline; Harajly et al, 2010; Rogers et al, 2011). Plasmid-mediated transfer of drug-resistance genes among various bacterial species is considered to be one of the most important mechanisms driving the spread of multi-drug resistance (MDR) markers.…”
Section: Introductionmentioning
confidence: 99%
“…Those expressing an ESBL phenotype frequently carry genes encoding resistance to other commonly used antimicrobial drug classes (such as aminoglycosides, chloramphenicols, fluoroquinolones, or tetracycline; Harajly et al, 2010; Rogers et al, 2011). Plasmid-mediated transfer of drug-resistance genes among various bacterial species is considered to be one of the most important mechanisms driving the spread of multi-drug resistance (MDR) markers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, aac(69)-Ib-cr alone confers a degree of resistance sufficiently low that the MIC might not distinguish organisms that carry it from those that do not (Robicsek et al, 2006). Recently, Harajly et al (2010) described transconjugants with no elevation of MIC after the transfer of aac(69)-Ib-cr.…”
Section: A Barguigua and Others 1348mentioning
confidence: 99%
“…In the United Kingdom, Woodford et al (24) found that a CTX-M-15 epidemic strain had ceftazidime MICs consistently lower than those seen with other CTX-M-15 producers (MICs Յ 2 g/ml), placing them in the "susceptible" category by British Society of Antimicrobial Chemotherapy (BSAC) criteria (24). CTX-M-15 strains with variable levels of resistance to cefotaxime (MIC of 2 g/ml), ceftazidime (MIC 1.5 g/ml), and cefepime (MIC 1 to 2 g/ml) have also been isolated recently in hospitals in Belgium (11) and Lebanon (6). Previous studies have characterized the bla CTX-M-15 -containing plasmids (2,16) and have shown that bla CTX-M-15 alleles are located on plasmids downstream of an ISEcp1 element.…”
mentioning
confidence: 99%